AB1358-HPR SUICIDAL BEHAVIORS IN PATIENTS WITH INTRAVENOUS BIOLOGIC THERAPIES. (June 2019) - Esteban, Amparo Lopez; Gonzalez Benitez, Roberto Daniel; Amigo, Aurora Alonso; Amigo, Aurora Alonso; Sanchez Zanotti, Juan Carlos; Calle, Florentina Garca; Nieto, Juan Carlos; Benavente, Beln Serrano; Ovalles, Juan; Blasco, Tamara Del Ro; Ariza, Alfonso; Gonzalez, Carlos; et al.
Abstract : Background: In patients with rheumatic diseases, suicidal ideation (Si) and suicide attempt (Sa) have been observed more frequently than in the general population. Objectives: 1. To determine the prevalence of Si and Sa in patients with biological therapies. 2. To evaluate possible factors associated with the Si. Methods: Observational cross-sectional study in patients with intravenous BT from Day Hospital of a tertiary hospital in Madrid. Sociodemographic, disease features [weight, height, work disability (WD), diagnosis, treatment] and PRO (FiRST, FACIT-F, HAD, and GHQ-28) were collected. We defined the Si according to the answer at the 6 th and 7 th questions of section D of the GHQ-28. The Sa was registered according the patient`s clinical history. The categorical variables were analyzed with the Chi square test. A logistic regression analysis was performed to evaluate the possible factors associated with suicidal behavior (SB). To evaluate the variance of discrete quantitative variables between groups the Kruskal-Wallis test was used, with a post-hoc analysis with U-Mann Whitney, to determinate the difference between pairs. Results: We included 321 patients, 65% women, with a mean age (range, SD) of 56 years (89-15, 14.1), and a mean disease duration (range, SD) of 16 years, DS (53-1, 9.7). The sociodemographic and clinical characteristics are described in Table 1 and 2 . Of all patients, 4% had had 1 or more Sa and 11% had Si. 23% of patients had associated fibromyalgia (FiRST), 47% fatigue (FACIT-F), 27.4% anxiety (A-HAD), 16.2% depression (D-HAD) and a 48.6% a probable psychic disorder (GHQ-28). The final logistic regression model includes FACIT-F, IL, D-HAD, and first biological with Cox R 2 and Snell 20.1% and Nagelkerke 35.5%. The area under the curve was 0.849 with significance p <0.0001 [95% CI (0.786 - 0.912)]. Regarding the GHQ-28 score, a significant difference was observed among the diagnostic groups (p <0.001); in post-Hoc, a lower score was observed among patients with ankylosing spondylitis p <0.001. We also observed a significant difference among the treatment groups (p <0.001) for the GHQ-28 score. In the post-hoc analysis, the Abatacept group had a significantly higher mean p = 0.042 of GHQ-28 score, however, in the multivariate analysis no significant difference was observed p = 0.416. Conclusion: There is a high prevalence of Si and Sa in patients with BT. Depression, fatigue, sleep disorders, fibromyalgia and work disability were associated with a higher prevalence of SB. Disclosure of Interests: Amparo Lopez Esteban : None declared, Roberto Daniel Gonzalez Benitez: None declared, Aurora Alonso Amigo: None declared, Iustina Janta: None declared, Juan Carlos Sanchez Zanotti: None declared, Florentina Garca Calle: None declared, Juan Carlos Nieto: None declared, Beln Serrano Benavente: None declared, Juan Ovalles: None declared, Tamara Del Ro Blasco: None declared, Alfonso Ariza: None declared, Carlos Gonzalez Consultant for: Celgene, Gilead, Janssen, Merk, Novartis, Pfizer, Speakers bureau: Celgene, Roche, UCB, Indalecio Monteagudo Sez: None declared